Microbial community assembly patterns at the species level in different parts of the medium temperature Daqu during fermentation - Zhang Wen; Pei-Jie Han; Da-Yong Han; Liang Song; Yu-Hua Wei; Hai-Yan Zhu; Jie Chen; Zheng-Xiang Guo; Feng-Yan Bai (Current Research in Food Science)
Medium-temperature Daqu (MT-Daqu) serves as a crucial saccharifying and fermentation agent in the production of strong-flavor Baijiu. Due to the spatial heterogeneity of solid fermentation, significant differences occurred in the fermentation state and appearance features in different parts of Daqu during fermentation. Currently, the understanding of the underlying mechanism behind this phenomenon remains limited. Here, we analyzed the microbial succession and assembly models and driving factors in different parts of MT-Daqu at the species level based on the PacBio single-molecule real-time sequencing technology. The results showed significantly different bacterial and fungal community compositions, successions, and interaction patterns in different parts of MT-Daqu. The bacterial community composition and succession model in the middle layer were similar to those in the core layer, whereas the fungal community composition and succession model in the surface layer were similar to those in the middle layer. The co-occurrence network analysis showed that microbial interaction is stronger in the middle and core layers than in the surface layer. Analyses based on both niche theory and neutral theory models indicated that deterministic processes predominantly governed the microbial community assembly and these processes played an increasingly important role from the surface to the core layer. Random forest analysis revealed that temperature was the primary endogenous factor driving the bacterial and fungal community assembly. The results of this study contribute to a better understanding of the microbial community in MT-Daqu and are helpful for the quality control of MT-Daqu fermentation.